Pengaruh Media Sosial Terhadap Perilaku Konsumtif Generasi Z - Nur Annisa Sawitri; Ghina Rizki Amalia; Risma Anita Puriani (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
The rapid development of social media has influenced the lifestyle and consumption patterns of Generation Z, who grow up in a highly digital environment. The high intensity of social media usage makes this generation more vulnerable to exposure to trends, digital promotions, and influencer influences that potentially increase consumptive behavior. This study aims to analyze the influence of social media on the consumptive behavior of Generation Z using a library research method. The collected data were analyzed using a qualitative descriptive technique through the processes of identification, classification, and interpretation of findings from previous studies. The results indicate that social media contributes to increased consumptive behavior through the formation of digital lifestyles, influencer influence, popular culture, and the convenience of online transactions that encourage impulsive buying. However, digital literacy, self-control, and financial literacy function as controlling factors in consumption behavior. Therefore, educational efforts through guidance and counseling services as well as the strengthening of digital literacy are needed to help Generation Z develop more critical and rational consumption behavior in the digital era.